Assessing the emotional impact of virtual reality-based teacher training. Issue 3 (13th March 2019) - Stavroulia, Kalliopi Evangelia; Christofi, Maria; Baka, Evangelia; Michael-Grigoriou, Despina; Magnenat-Thalmann, Nadia; Lanitis, Andreas
Abstract : Purpose: The purpose of this paper is to propose the use of a virtual reality (VR)-based approach to improve teacher education and life-long professional development. Through constant training in real-life based situations but within a safe three-dimensional virtual school environment, teachers are given the opportunity to experience and learn how to react to different types of incidents that may take place in a school environment. Design/methodology/approach: The current paper presents the design cycle that was followed for the implementation of the VR teacher training system. The effectiveness of the proposed approach is demonstrated with a case study that aimed to promote teachers' understanding of student's problematic situations related to substance use. As part of the experimental investigation, the impact of the VR system on participants' emotions and mood states is evaluated through Electroencephalogram (EEG) measurements, heart rate (HR) recordings and self-reported data. Findings: Results indicate significant changes to participant's negative emotional and mood states, suggesting that the scenario and the VR experience had a strong impact on them. Moreover, participants' HR was increased during the experiment, while the analysis of the EEG signal indicated that the participants experienced a stressful situation that could justify the change in their negative emotions and mood states. Originality/value: The proposed VR-based approach aims to provide an innovative framework to teacher education and the related training methodology. In the long-term, the proposed VR system aims to form a new paradigm of teacher training, an alternative safe method that will allow user-teachers to learn through trial and error techniques that reflect real-life situations within a three-dimensional school space and without the risk of harming real students. To the best of our knowledge this is one of the first systematic attempts to use a VR-based methodology to address real teachers' needs. The development of the VR application is linked to both strong theoretical foundations in education derived from the literature but also from real teachers' problems and requirements derived from an extensive literature analysis, survey and interviews with experts including teachers, school counselors and psychologists. The VR tool addresses specific teachers' competences as outcome, after an extensive documentation of existing Teachers' Competence Models and significant guidance by experts who pointed specific competencies of primary importance to teachers.